Three-inch teeth [compact disc, unabridged] - Box, C. J. (Box, C. J. Joe Pickett novel., 2024)
A grizzly bear is on a rampage. At the same time, a newly released criminal wants revenge on the people who put him away, including game warden Joe Pickett. The bear attacks are the perfect cover.